Measurement of the inclusive jet cross section in pp collisions at √s=7TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2011)
The inclusive jet cross section is measured in pp collisions with a center-of-mass energy of 7 TeV at the Large Hadron Collider using the CMS experiment. The data sample corresponds to an integrated luminosity of 34pb -1. The measurement is made for jet transverse momenta in the range 18-1100 GeV and for absolute values of rapidity less than 3. The measured cross section extends to the highest values of jet pT ever observed and, within the experimental and theoretical uncertainties, is generally in agreement with next-to-leading-order perturbative QCD predictions. © 2011 CERN, for the CMS Collaboration. Published by the American Physical Society under the terms of the uri xlink:href=http://creativecommons.org/licenses/by/3.0/ Creative Commons Attribution 3.0 License. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI.